Emotional empowerment through information research and communication to reduce fear of COVID-19 among nursing students: a randomised controlled trial - L. Iván Mayor-Silva; Guillermo Moreno; Pedro R. Girón-Daviña; Samir Mohamedi-Abdelkader; Marta M. Hernández-Martín; Antonio G. Moreno-Pimentel; Alfonso Meneses-Monroy (BMC, 2023)
Abstract Background Despite an existing body of literature on anxiety reduction using multi-component methods, little is known about the effect of active student participation in research and communication of scientific information on anxiety and fear reduction. The aim of this study is to evaluate the impact of quality scientific information research and the production of informative videos on the preventive aspects of COVID-19 on fear and anxiety reduction. Methods A randomised controlled trial was conducted with 220 undergraduate nursing students in the first year of the nursing degree. The participating students were randomised into two groups. The experimental group carried out an intervention based on a database search for information on preventing COVID-19 and production of a video giving scientific reasons why prevention measures should be followed. In the control group, students created posters and videos about theoretical aspects of one module of the nursing degree. Both groups were surveyed before and after the intervention, measuring their state of resilience, preventive behaviours, level of anxiety, and fear of COVID-19. Results The intervention group showed a greater decrease in fear levels after the intervention than those in the control group. There were no differences between the groups in terms of resilience, preventive behaviours, or anxiety. In the experimental group, there was a significant decrease in anxiety levels and fear levels after the intervention compared to the baseline levels. Conclusions An intervention based on active participation in searches for high-quality scientific information and production of information videos on COVID-19 prevention reduced fear and anxiety caused by COVID-19 among nursing students. Trial registration We have retrospectively registered the trial in Open Science Framework and the identification number is https://doi.org/10.17605/OSF.IO/6QU5S .